Utilization of the principal trophic anions by the marine unicellular algae as a function of the specific environmental conditions - Mihnea, Pia Elena; Voinescu, Iulia (Cercetări Marine - Recherches Marines, 2026)
The results of the experiments on the utilization of trophic anions N (-NO3, -NO2) and P (_PO4) by the unicellular algae Cyclotella caspia GRUN. and Chaetoceros simplex var. calcitrans PAULS, are presented in this paper. The dependence of the influx-efflux phenomena on the specific temperature of the synthesis process of the two organisms, as well as on the total salt gradient value in the medium is thought. The ability of the algae to take part in the processes of the nitrogen state modification is discussed, together with the form of nitrogen storage in the cells.